Religious experience and uncertainty in postsecular societies (Journal of the Sociology and Theory of Religion, 2018)
The article analyzes some studies on western society. They describe it as "secular" / "postsecular" and characterize it by "uncertainty." Located on this horizon, and from a perspective of Catholic theology, the need to promote "action spaces" that allow a personalization of religious experience and thus promote human and social promotion will be argued. Anthropological and epistemological keys will be offered to show that, among these "spaces of action", there is personal and community Christian witness. The conclusion will be propositive, pointing out some suitable categories for the translation of these keys to social life.
Keywords: Religion; personal and community faith; testimony; meeting; membership